Interleukin-1 production by immunologically hyporeactive tumour-bearing mice - Holán, V; Lipoldová, M (British journal of cancer, 1990)
Mice bearing progressively growing syngeneic methylcholanthrene-induced sarcomas are immunologically hyporeactive. However, both basal (steady-state) and bacterial lipopolysaccharide (LPS)-induced synthesis of mRNA for interleukin-1 (IL-1) in peritoneal exudate cells (PEC) or spleen cells were comparable in control and tumour-bearing animals. Furthermore, the production of IL-1 by PEC stimulated with LPS in the presence of indomethacin was same in control and tumour-bearing mice. The results thus demonstrate that LPS-stimulated cells from animals bearing progressively growing syngeneic sarcomas synthesise the same quantities of mRNA for IL-1 and produce comparable amounts of IL-1 as do cells from normal animals, in spite of the profound immunological hyporeactivity of the former.
Keywords: messenger RNA; Tumor Cells, Cultured; ascitická tekutina; Immune Tolerance; experimentální sarkom; zvířata; myši; myši inbrední C57BL; Mice; nádorové buňky kultivované; RNA, Neoplasm; RNA, Messenger; RNA nádorová; Male; Mice, Inbred C57BL; imunologická tolerance; Animals; Interleukin-1; mužské pohlaví; Sarcoma, Experimental; interleukin-1; Ascitic Fluid